Why are infectious and parasitic diseases among the leading causes of death in Brazil? (Research, Society and Development, 2022)
Infectious and Parasitic Diseases (IPD) are part of a range of diseases that afflict public health in regions of less developed countries, where living and hygiene conditions are precarious. Among those affected, children represent a significant percentage and usually have malnutrition that delays physical and psychosomatic development. In this research, the objective was to draw a parallel between the occurrence of deaths in Brazil whose cause was infectious and parasitic diseases described in Chapter I of the ICD-10 and the relationship of this factor with the reports of other studies that point to the lack of basic sanitation, education, and poverty. The study presented here is a systematic review of the meta-synthesis type, approaching data from articles found in PubMed and VHL databases, using the PRISMA methodology criteria and the elaboration of a flowchart with the identification, exclusion, selection, and inclusion of data. . Also, data tabulation was performed on TABNET and IBGE to obtain quantitative information about the proposed theme. Data from the study indicate that infectious and parasitic diseases are the second leading cause of death in Brazil, representing about 17% of the total. In summary, this factor is associated with socio-economic issues and the accentuated deficit in economic terms that directly impacted access to education, food security, and basic sanitation; which causes cycles of transmission of infectious and parasitic diseases that are not diagnosed or have a late diagnosis and, consequently, are not treated, leading patients to death.